Individualization of Learning: An Investigation on Educational Technologies - Karpenko, Olga Mikhailovna; Lukyanova, Anna Viktorovna; Bugai, Vasily Vladimirovich; Shchedrova, Irina Alekseevna (Journal of History Culture and Art Research, 2019)
The paper discusses various approaches to the concept of “individualization of learning” and their relevant changes in connection with the development of educational technologies. An analysis of the relevant literature shows that a more precise content of this concept in each specific case depends on what goals are meant when talking about individualization. There are large differences found in different countries, among different authors, and in everyday educational practice when this concept is used. More than that, the authors demonstrate that the very notion of “individualization of learning” is replaced by “individual learning,” i.e. by the concept of “independently performing learning tasks.” The research also clearly shows that a number of opportunities for better individualization of training are limited in conditions of traditional didactics, as well as in terms of group work and the existing system of lectures and seminars. The authors argue that “individualized learning” is a part of “personalized learning,” since personalization is the realization of a person’s desire to be a person. And personality is a systemic quality of an individual. This quality appears in three spaces, one of which is the space of a person’s individual life. Another claim is that full individualization of potentials existing in education can only be achieved through a didactic-technological paradigm based on web-technology and application of intelligent robots in education. The second requirement implies administration of both education and educational process management. The authors additionally provide a case study of the “LUNCH Intellectual Information System” in order to support their arguments.